Boosting children's creativity through creative interactions with social robots - Alves-Oliveira, P. (2016)
Creativity is one of the most important and pervasive of all human abilities. However, it seems to decline during school age years, in a phenomenon entitled “creative crisis”. As developed societies are shifting from an industrialized economy to a creative economy, there is a need to support creative abilities through life. With this work, we aim to use social robots as boosters for creative-driven behaviors with children.